THE DIGITAL LEAP: STRATEGIC MANAGEMENT FOR DIGITAL TRANSFORMATION SUCCESS IN TRADITIONAL INDUSTRIES - Septian Aryatama; Dianawati Suryaningtyas; Martanto Martanto; Arif Budi Sulistyo; Khotimatul Barki (Branding: Jurnal Manajemen dan Bisnis, 2024)
Digital transformation in traditional industries is an important step to remain competitive in the modern era. The application of digital technology in business operations can increase efficiency and provide a better customer experience. However, many traditional companies face challenges in adopting new technologies and developing digital skills. This research aims to explore the role of strategic management in supporting the success of digital transformation in traditional industries. This research uses a qualitative approach, with data obtained from the results of relevant research and previous studies. The collected data will be analyzed to find significant patterns and relationships. The research results show that a clear digital vision and strategy are critical to guiding transformation. Effective leadership and good change management are also crucial in overcoming internal resistance. Implementing digital technologies, such as automation and analytics, can significantly improve operational efficiency. The development of digital skills and competencies through continuous training and external collaboration is essential to support this change. With a comprehensive approach, traditional companies can overcome the challenges of digital transformation and take advantage of the opportunities offered by new technologies.